3 - Faculty Governance: Opportunities and Challenges after the Egyptian Revolution – The case of the FEPS, Cairo University - Hala H. El Said (Journal of Higher Education in Africa, 2014)
Higher education had always been a top priority in Egypt since the 1952 revolution. In this paper, we will have an overview of the higher education system in Egypt highlighting the main challenges facing this system and the possible areas of reform. Governance of the Faculty of Economics and Political Sciences (FEPS) will be discussed as a case study. Finally, a set of recommendations are mentioned to conclude this paper.